PENGEMBANGAN MEDIA PEMBELAJARAN INTERAKTIF PADA KETERAMPILAN MENULIS PENGUMUMAN MENGGUNAKAN SMART APPS CREATOR DI KELAS V SEKOLAH DASAR - Fauziah, Aisyah; Muhammadi, Muhammadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the less than optimal use of technology in using learning media according to current developments. This research aims to develop interactive learning media on announcement writing skills using Smart Apps Creator in class V elementary schools that is valid, practical and effective. This type of research is development research with the ADDIE model. Data collection uses validation sheets, response questionnaires, and evaluation sheets. The test subjects were class V students consisting of 12 students from SD Negeri 12 Padang Besi and 16 students from SD Negeri 21 Bandar Buat. The results of this research showed that media had a validity of 94.44% for material, 91.66% for language, and 92.24% for media with an average of 92.78% (very valid). The results of the practicality of teacher responses obtained an average of 95.31%. Meanwhile, the practicality of responses from class V students at SD Negeri 12 Padang Besi obtained a result of 94.44% (very practical) and at SD Negeri 21 Bandar Buat obtained a result of 96.09% (very practical). The results of media effectiveness in class V of SD Negeri 12 Padang Besi obtained an increase in learning outcomes of 87.5% with completeness of 79.16%. Meanwhile, class V at SD Negeri 21 Bandar Buat achieved an increase in learning outcomes of 90.62% with a completeness of 81.25%. It can be concluded that interactive learning media on announcement writing skills using Smart Apps Creator in class V elementary school has proven to be valid, practical and effective.